Interactions of antiretroviral drugs with the SLC22A1 (OCT1) drug transporter - Darren eMoss; Neill eLiptrott; Marco eSiccardi; Andrew eOwen (Frontiers Media S.A., 2015)
The SLC22A1 influx transporter is expressed on the basolateral membrane of hepatocytes and is involved in the excretion of numerous cations. Inhibition of SLC22A1 by several antiretrovirals, such as the protease inhibitor darunavir, has not previously been determined. In order to better understand and predict drug-SLC22A1 interactions, a range of antiretrovirals were screened for SLC22A1-associated inhibition and transport. Stable SLC22A1-expressing KCL22 cells were produced previously by nucleofection. Control KCL22 cells were transfected with the empty vector pcDNA3.1. Accumulation of tetraethylammonium (5.5 µM, 30 min) was determined in SLC22A1-expressing and mock-transfected cells with and without 50 µM of SLC22A1 inhibitor prazosin, or 50 µM of each antiretroviral drug. SLC22A1 IC50 values for efavirenz, darunavir and prazosin were determined. Cellular accumulation of efavirenz and darunavir was also assessed in SLC22A1-expressing KCL22 cells and reversibility of this accumulation was assessed using prazosin. Tetraethylammonium accumulation was higher in SLC22A1-expressing cells compared to mock-transfected cells (10.6±0.8 µM versus 0.3±0.004 µM, p=0.009) and was significantly reduced in SLC22A1-expressing cells when co-incubated with all antiretrovirals tested except atazanavir, lamivudine, tenofovir, zidovudine and raltegravir. Particularly noticeable was the predominance of SLC22A1 inhibitors in the protease inhibitor and non-nucleoside reverse transcriptase inhibitor classes. Absolute SLC22A1 IC50 values for efavirenz, darunavir and prazosin were 21.8, 46.2 and 2.8 µM, respectively. Efavirenz accumulation was higher in SLC22A1-expressing cells compared to mock-transfected cells (17% higher, p = 0.009) which was reversed using prazosin, whereas no difference was observed for darunavir (p=0.86). These data inform the mechanistic basis for disposition, drug-drug interactions and pharmacogenetic candidate gene selection for antiretroviral drugs.